Filozofia prawa natury w katolickiej myśli społecznej, gospodarczej i politycznej. Wybrane zagadnienia prawne i społeczne - Nikołajew, Jerzy (Przegląd Prawno-Ekonomiczny, 2013)
Streszczenie dostępne wyłącznie w języku angielskim: The subject of this discussion is the issue of philosophy of natural law covered by Catholic social, economic and political thought. In the introduction, the author refers to the concept of natural law. Especially to those powers which relate to the right of ownership, the right to property, the right to maintain life and the right to the fruits of one’s own work. Then, he touches upon the issue of ownership, as seen in the Old and New Testament and by early Christian communities. He draws particular attention to the Old Testament Jewish law and the Ten Commandments as well as Jewish and Christian communities. Later, he analyses the views of St Thomas on the issues of the interrelationship between natural law and private property, almsgiving and usury. At this point, the author articulates the importance of theological and philosophical thought of Aquinas in building future concepts of the Catholic Church’s social science. Further considerations pertain to views on matters related to natural law and ownership in the teaching of successive popes in recent centuries. First, the author reviews the encyclical Rerum Novarum, indicating its fundamental importance in this matter. Then, he analyses the encyclical of Pius XI, especially in the context of property as understood by the socialists. Further discussion relates to the social teaching of Pope Pius XII, John XXIII and Paul VI. A separate analysis is devoted to John Paul II and his understanding of natural law in the sphere of economic and social activity. Next, the author focuses on the teaching of Benedict XVI and the encyclical Caritas in Veritate. Considerations end with the indication of the fundamental importance of respecting the property as the foundation of the Catholic social teaching.